Penerapan Etika Bisnis Islam pada Pedagang Sembako di Desa Jumbleng Indramayu - Wahyu Sri Bintang Romadona; Izzani Ulfi (JMK (Jurnal Manajemen dan Kewirausahaan), 2021)
Sembako (nine staple foods) is basic needs that must be fulfilled in order to maintain the food security and nutritional needs of the community. Therefore, sembako traders have an important role in how sembako items are properly distributed to the community. In achieving this goal, it is suggested that the traders operate based on an ethical business framework. Islam through the Qur'an and hadith has provided this framework in the form of Islamic business ethics principles. By using a qualitative descriptive analytical approach, this study aims to understand how the application of Islamic business ethics in the business activities of basic food traders in Jumbleng Village. The data in this study were collected through a process of observation and interviews. While the data analysis technique uses the analytical technique developed by Miles, Huberman, & Saldana with the stages of data reduction, data presentation, and drawing conclusions. Based on the results of research obtained from traders and buyers in Jumbleng Village, it shows that the principles of Islamic business ethics have not been fully implemented by traders due to their limited knowledge regarding Islamic business ethics.